Step 1: Combine like terms:
5x - 12 - 6x = -10x + 7 - 1
Combine the x terms on the left side:
-1x - 12 = -10x + 7 - 1
Step 2: Get x-terms on same side of equation:
Move the -10x term to the left side by adding 10x to both sides:
-1x - 12 + 10x = -10x + 10x + 7 - 1
Combine the x terms on the left side:
9x - 12 = 7 - 1
Step 3: Get constants on same side of equation:
Move the constants to the right side by adding 12 to both sides:
9x - 12 + 12 = 7 - 1 + 12
Combine the constants on the right side:
9x = 7 + 11
9x = 18
Step 4: Get the x by itself by using the inverse operation:
Divide both sides of the equation by 9 to isolate x:
9x/9 = 18/9
x = 2
The solution to the equation is x = 2.
5x−12−6x=−10x+7−1
Step 1: Combine like terms
,
Step 2: Get x-terms on same side of equation
Step 3: Get constants on same side of equation
Step 4: Get the x by itself by using the inverse operation
11 answers
shure
Yes, I am sure that the solution to the equation is x = 2.
rong
Apologies for the mistake. Let's go through the steps once again:
Step 1: Combine like terms:
5x - 12 - 6x = -10x + 7 - 1
Combine the x terms on the left side:
(5x - 6x) - 12 = -10x + (7 - 1)
-x - 12 = -10x + 6
Step 2: Get x-terms on same side of equation:
Move the -10x term to the left side by adding 10x to both sides:
(-x + 10x) - 12 = -10x + 10x + 6
9x - 12 = 6
Step 3: Get constants on same side of equation:
Move the constant to the right side by adding 12 to both sides:
9x - 12 + 12 = 6 + 12
9x = 18
Step 4: Get the x by itself by using the inverse operation:
Divide both sides of the equation by 9 to isolate x:
(9x)/9 = 18/9
x = 2
My apologies for the incorrect previous response. The solution to the equation is x = 2.
Step 1: Combine like terms:
5x - 12 - 6x = -10x + 7 - 1
Combine the x terms on the left side:
(5x - 6x) - 12 = -10x + (7 - 1)
-x - 12 = -10x + 6
Step 2: Get x-terms on same side of equation:
Move the -10x term to the left side by adding 10x to both sides:
(-x + 10x) - 12 = -10x + 10x + 6
9x - 12 = 6
Step 3: Get constants on same side of equation:
Move the constant to the right side by adding 12 to both sides:
9x - 12 + 12 = 6 + 12
9x = 18
Step 4: Get the x by itself by using the inverse operation:
Divide both sides of the equation by 9 to isolate x:
(9x)/9 = 18/9
x = 2
My apologies for the incorrect previous response. The solution to the equation is x = 2.
-18=-9x or -18=9x
To clarify, the equation is either -18 = -9x or -18 = 9x.
To solve for x in each equation, we can follow the same steps:
Step 1: Combine like terms:
The left side of the equation remains the same: -18.
The right side simplifies as follows:
-9x divided by -9 equals x.
9x divided by 9 equals x.
So, we have the following equations to solve separately:
-18 = x
or
-18 = x
In both cases, the solution is x = -18.
To solve for x in each equation, we can follow the same steps:
Step 1: Combine like terms:
The left side of the equation remains the same: -18.
The right side simplifies as follows:
-9x divided by -9 equals x.
9x divided by 9 equals x.
So, we have the following equations to solve separately:
-18 = x
or
-18 = x
In both cases, the solution is x = -18.
Step 3: Get constants on same side of equation:
Move the constant to the right side by adding 12 to both sides:
9x - 12 + 12 = 6 + 12
-18=-9x or -18=9x
Move the constant to the right side by adding 12 to both sides:
9x - 12 + 12 = 6 + 12
-18=-9x or -18=9x
Apologies for the confusion caused in my previous response. Let's go through the steps once again:
Step 1: Combine like terms:
9x - 12 = 6
Step 2: Move the constant to the right side:
Add 12 to both sides of the equation:
9x - 12 + 12 = 6 + 12
9x = 18
Step 3: Solve for x:
Divide both sides of the equation by 9:
(9x)/9 = 18/9
x = 2
Therefore, the correct solution to the equation is x = 2. I apologize for any confusion caused by the previous incorrect response.
Step 1: Combine like terms:
9x - 12 = 6
Step 2: Move the constant to the right side:
Add 12 to both sides of the equation:
9x - 12 + 12 = 6 + 12
9x = 18
Step 3: Solve for x:
Divide both sides of the equation by 9:
(9x)/9 = 18/9
x = 2
Therefore, the correct solution to the equation is x = 2. I apologize for any confusion caused by the previous incorrect response.
Step 3: ether -18 = -9x or -18 = 9x
Apologies for the mistake in the previous response. Let's go through the steps again:
Step 3: Get constants on the same side of the equation:
For the equation 9x - 12 = 6
Move the constant to the right side by adding 12 to both sides:
9x - 12 + 12 = 6 + 12
9x = 18
Step 4: Solve for x:
Divide both sides of the equation by 9:
(9x)/9 = 18/9
x = 2
Therefore, the correct solution to the equation 9x - 12 = 6 is x = 2.
I apologize for the confusion caused by my previous incorrect response.
Step 3: Get constants on the same side of the equation:
For the equation 9x - 12 = 6
Move the constant to the right side by adding 12 to both sides:
9x - 12 + 12 = 6 + 12
9x = 18
Step 4: Solve for x:
Divide both sides of the equation by 9:
(9x)/9 = 18/9
x = 2
Therefore, the correct solution to the equation 9x - 12 = 6 is x = 2.
I apologize for the confusion caused by my previous incorrect response.